Lontar Sri Tanjung: Narasi, Simbol, dan Ingatan - Wiwin Indiarti (Manuskripta, 2025)
Lontar Sri Tanjung is a classical Nusantara manuscript that weaves narrative, moral teachings, and symbolism, serving as a vital repository of cultural memory for the Banyuwangi region and Osing community. Its recognition as an Indonesian National Collective Memory (IKON) in 2024 affirms its significance in preserving intangible heritage. The text recounts the legendary origin of Banyuwangi through the symbol of fragrant water, embodying values of loyalty, sacrifice, and the honor restoration. Central to the story is an idealized female figure who reflects traditional moral ideals while anchoring local cultural identity. Viewed through the lens of collective memory studies, Lontar Sri Tanjung is not a static relic but a living cultural space that continually shapes and transmits shared meanings across generations. Contemporary critical readings open possibilities for reinterpretation, including discussions of gender and power. Today, the manuscript remains relevant for character education, cultural literacy, reinforcing local identity, and advancing cultural diplomacy. === Lontar Sri Tanjung merupakan naskah sastra klasik Nusantara yang memadukan narasi, nilai moral, dan simbolisme, sekaligus berfungsi sebagai memori budaya masyarakat Banyuwangi dan Osing. Penetapannya sebagai naskah Ingatan Kolektif Nasional (IKON) 2024 menegaskan perannya sebagai naskah penting dalam pelestarian warisan budaya. Kisah Sri Tanjung memuat legenda asal-usul Banyuwangi melalui simbol air harum, serta nilai kesetiaan, pengorbanan, dan pemulihan kehormatan. Narasi ini menghadirkan figur perempuan ideal dalam bingkai moral tradisional, sekaligus merefleksikan identitas kultural masyarakat setempat. Dalam kajian ingatan kolektif, Lontar Sri Tanjung bukan sekadar arsip masa lalu, melainkan ruang hidup yang membentuk dan mereproduksi ingatan lintas generasi. Pembacaan kritis memungkinkan penafsiran ulang dalam konteks kontemporer, termasuk isu gender dan relasi kuasa. Di masa kini, naskah ini relevan untuk pendidikan karakter, literasi budaya, penguatan identitas lokal, dan diplomasi budaya.